Knowledge, attitude and practices of institution-based dentists toward nicotine replacement therapy - Swikant Shah; Hemamalini Rath; Gaurav Sharma (Wolters Kluwer Medknow Publications, 2017)
Background: Dental institutions provide very good platform to educate budding dentists to inculcate the habit of tobacco cessation counseling, including nicotine replacement therapy (NRT). Aims: The aim of this study is to assess and compare the knowledge, attitude, and practice of institutionally attached postgraduate students and faculty members of the dental profession toward NRT. Methods: For a cross-sectional survey among 201 participants from four dental colleges in Odisha, India, a 28-item questionnaire was developed, subdivided into four categories: demographic details, assessment of NRT knowledge (21-item), assessment of attitude (5-item), practice (1-item with 4 subgroup questions), and 1-item assessing barriers. Statistical Analysis Used: Data were analyzed using descriptive statistics, Chi-square test, and multiple logistic regression. Results: Only one-third of participants were aware of the dosage, mechanism of action, pharmacology, duration of the prescription, brand name, side effects, contraindications, and availability. Around two-third of participants who claimed to practice NRT, agreed to follow up the patients whom they prescribed NRT. Half of the study participants reported that they do not keep a record of these patients. Around 10% of respondents practicing NRT were confident enough to practice it without facing any problem. Major barriers for practicing NRT was found to be a lack of awareness (54.22%) followed by availability and bitter taste. The total knowledge score was found to be the strongest predictor of practicing NRT in multiple logistic regression. Conclusion: Lack of detailed knowledge regarding NRT reduces the chance of practicing inspite of having a positive attitude among institutionally attached dentists.